Charcot–Marie–Tooth disease type 2A with an autosomal-recessive inheritance: the first report of an adult-onset disease. Issue 1 (January 2018) - Hikiami, Ryota; Yamashita, Hirofumi; Koita, Natsuko; Jingami, Naoto; Sawamoto, Nobukatsu; Furukawa, Kaoru; Kawai, Hiromichi; Terashima, Tomoya; Oka, Nobuyuki; Hashiguchi, Akihiro; Takashima, Hiroshi; Urushitani, Makoto; et al.
Abstract Axonal Charcot–Marie–Tooth disease (CMT) is most frequently caused by mutations in theMFN2 gene (CMT2A) that can lead to various clinical phenotypes. The age at disease onset varies, but most cases occur before adolescence. We report two Japanese sisters who presented with middle-age-onset peripheral neuropathy with distinct clinical features. In the affected sisters, a homozygous missense mutation, c.1894C>T, p.R632W, corresponding to the transmembrane domain ofMFN2 was identified; this mutation was heterozygous in another non-affected sibling, demonstrating co-segregation of the genotype and phenotype. The patients developed adult-onset slowly progressive muscle weakness that was predominant in the calf muscles and sensory disturbance. Magnetic resonance imaging revealed diffuse atrophy of the spinal cord, especially in the thoracic segment, and mild atrophy of the parietal lobe and the cerebellum in both patients. Electron microscopy of the sural nerve revealed clusters of round and swollen mitochondria. This is the first case report of adult-onset CMT2A with an autosomal-recessive inheritance pattern. The phenotype caused by theMFN2 mutation in these cases is very mild, considering that the mutation causes middle-aged-onset Charcot–Marie–Tooth even in the homozygous state. The mechanism ofMFN2 mutation-induced toxicity is an interesting theme that awaits further investigations.